PROSPEK PENGEMBANGAN INDUSTRI KECIL TAHU “BAROKAH” DI KELURAHAN OEKEFAN KECAMATAN KOTA SOE KABUPATEN TIMOR TENGAH SELATAN - Deni Junita Selan; Marthen R. Pellokila; Lika Bernadina (Undana Press, 2022)
The purpose of this study was to determine the performance of the business, how efficient is the business, and how the prospects for the development of the “Barokah” Tofu Small Industry in Oekefan Village, Soe City District, South Central Timor Regency in the future. The types of data used in this study are primary and secondary data. The results showed that performance analysis was used to determine the type of production produced, marketing and profits in the small industry of